2020
DOI: 10.1017/s0007114520002251
|View full text |Cite
|
Sign up to set email alerts
|

Urea supplementation in rumen and post-rumen for cattle fed a low-quality tropical forage

Abstract: We evaluated the differences between the supplementation of urea in rumen and/or abomasum on forage digestion, nitrogen (N) metabolism, and urea kinetics in cattle fed a low-quality tropical forage. Five Nellore heifers were fitted with rumen and abomasum fistulas and assigned to a Latin square design. The treatments were: control, continuous infusion of urea in the abomasum (AC), continuous infusion of urea in the rumen, a pulse dose of urea in the rumen every 12 hours (PR), and a combination of PR and AC. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 57 publications
5
14
0
Order By: Relevance
“…Steers supplemented with conventional urea (TP-U) had lower concentrations of ammoniacal nitrogen in the rumen, and higher concentrations of urea present in the blood. Different results were found by [ 12 ], who reported that the highest concentration of ammoniacal nitrogen occurred when urea was supplied totally or partially in the rumen. According to [ 60 ], there are changes regarding the blood parameters linked to the species, leading to variations between breeds, as well as between the age groups of the animals.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Steers supplemented with conventional urea (TP-U) had lower concentrations of ammoniacal nitrogen in the rumen, and higher concentrations of urea present in the blood. Different results were found by [ 12 ], who reported that the highest concentration of ammoniacal nitrogen occurred when urea was supplied totally or partially in the rumen. According to [ 60 ], there are changes regarding the blood parameters linked to the species, leading to variations between breeds, as well as between the age groups of the animals.…”
Section: Discussionmentioning
confidence: 67%
“…When evaluating the effect of urea infusion in the abomasum of cattle, the TP-PRU group had a lower pH average. In this line, [ 12 ], animals that received urea by direct infusion into the abomasum had lower pH averages, with one positive effect, as previously mentioned, by decreasing the permeability of the rumen and thus maintaining a more adequate nitrogen supply for microbial growth in the rumen. Ref.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, poor digestibility fodder grasses can be improved by adding urea supplements into an animal diet 65 . Some other studies also supported the fact that by addition of urea as a supplement can improve the digestibility of low quality forages 87 , 88 .…”
Section: Discussionmentioning
confidence: 77%
“…is meant that carbohydrate fermentation in the rumen increased, whereas urea had no effect on microbial growth [31]. e greater NH 3 -N content from urea decomposition and readily carbohydrate fermentation from fresh cassava root supplementation may have resulted in a beneficial effect on total VFA with urea addition, creating a better Veterinary Medicine International environment for ruminal development [32,33]. Similarly, Khattab et al [34] found that adding 0, 10, and 15 g/kg urea, while Supapong and Cherdthong [9] found that adding 10 and 20 g/kg urea considerably boosted total VFA synthesis.…”
Section: Discussionmentioning
confidence: 99%